Ethnobotanical Study of Indigenous Plants used by the Members of Mantheding Community in Limpopo Province, South Africa - Sejabaledi Agnes Rankoana (E-Journal of Humanities, Arts and Social Sciences, 2022)
This study is an ethnobotanical survey conducted in the Limpopo Province (South Africa) with the goal of collecting detailed information about the cultural significance of indigenous plants in human culture. Three hundred and forty semi-structured interviews with traditional health practitioners and community members knowledgeable about plant use yielded ethnobotanical data on a variety of indigenous plant uses. The ethnobotanical data collected produced 77 species belonging to 31 families. The diversity of plants produced 45 sources of medicine, 17 sources of stock feed, 13 sources of technological materials, 10 food sources, and six fuel sources. It was found that most plants (15.5%) have dual uses as sources of food and fodder, as well as sources of fruits that are also used for medicinal purposes and timber for the manufacturing of household utensils. The study findings demonstrated how traditional knowledge about indigenous plants may be leveraged to address some of society’s most pressing issues, including food insecurity, poor health and wellbeing, poverty, and unemployment. The study reported that the rural community’s continued dependence on indigenous plant materials for subsistence is an example of cultural resilience in the pursuit of sustainable development. The research is crucial because it provides information on the plants that remain prominent in Mantheding culture and their many uses in the community’s culture.